STUDI EMPIRIS PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN PELATIHAN TERHADAP KINERJA YANG DIMEDIASI MOTIVASI DAN DIMODERASI LOCUS OF CONTROL (Studi pada Pegawai Kantor Dinas Pendidikan dan Kebudayaan Kota Probolinggo) - Nurul Afriningsih; Nasharuddin Mas; Gunarianto, Gunarianto (Bajang Institute, 2025)
This study aims to empirically analyze the influence of transformational leadership and training on performance mediated by motivation and moderated by locus of control. The population in this study were all Civil Servants of the Probolinggo City Education and Culture Office totaling 56 people and the number of samples was determined by total sampling. The data analysis technique used in this study was Partial Least Square-Structural Equation Modeling (PLS-SEM) using smartPLS software. The results of the study indicate that transformational leadership is not able to improve performance. Transformational leadership is able to improve motivation. Training is not able to improve performance. Training is able to improve motivation. Motivation is able to improve performance. Locus of control is able to improve performance. Transformational leadership is able to improve performance that is fully mediated by motivation. Training is able to improve performance that is fully mediated by motivation. Transformational leadership is able to improve performance that is pseudo-moderated by locus of control. Training is not able to improve performance that is moderated by predictors by locus of control